Analisis dan Identifikasi Sektor Potensial di Kabupaten Pangandaran (Studi Kasus Tahun 2014-2020) - Budi Hadiansyah; IGP Randy Aditya Mandala (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2021)
Kabupaten Pangandaran is the youngest regency in West Java. It is located at the southern tip of Jawa Barat with Pangandaran Beach as its leading tourist destination. Kabupaten Pangandaran continues to improve running the economy to contribute to the GDP Regional of Jawa Barat Province. The purpose of this research is to identify potential sectors that are feasible to be developed in Kabupaten Pangandaran. This research used analitycal the economic base model through Location Quotient (LQ) analysis combined with Shift-Share analysis which ends in the Sectoral Typology analysis. Based on the results, there are six potential economic sectors (Typology I ) that deserve to be prioritized in Kabupaten Pangandaran in order to increase economic growth in the region. These six economic sectors have an LQ index greater than 1 (the base sector) and the proportional and differential components are positive. These are: 1) Wholesale and Retail Trade, Car and Motorcycle Repair; 2) Transportation and Warehousing Sector; and 3) Accommodation and Food and Drink Sector; 4) Real Estate Sector; 5) Government Administration, Defense and Mandatory Social Security Sector; and 6) Corporate Services Sector.